2022
DOI: 10.32388/mz3cof
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Immediate test-retest reliabilities of intention to quit smoking measures in current adult smokers

Abstract: BACKGROUND: The Stages of Change (SOC) measure and Motivation To Stop Scale (MTSS) are regularly used to capture current smokers’ intention to quit (ITQ) cigarette smoking. They were shown to have comparable performances in construct and predictive validity, but their immediate test-retest reliabilities have not been investigated. In this randomized online two-arm study, we examined the immediate test-retest reliability of both SOC and MTSS measures. METHODS: Adult current smokers were randomized to complete … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Finally, action (1 day to 6 months of abstinence from smoking) and maintenance (more than 6 months of abstinence) stages would go beyond readiness to change and require actually making the behavior change of quitting smoking. Stage classification has shown high short-term retest reliability 3 , 4 and has proven useful as a predictor of behavior change. For example, a secondary analysis of five smoking cessation trials found that 37% of those in the preparation stage at baseline were abstinent at 24-month follow-up, compared to 26% of contemplators and 16% of precontemplators.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, action (1 day to 6 months of abstinence from smoking) and maintenance (more than 6 months of abstinence) stages would go beyond readiness to change and require actually making the behavior change of quitting smoking. Stage classification has shown high short-term retest reliability 3 , 4 and has proven useful as a predictor of behavior change. For example, a secondary analysis of five smoking cessation trials found that 37% of those in the preparation stage at baseline were abstinent at 24-month follow-up, compared to 26% of contemplators and 16% of precontemplators.…”
Section: Introductionmentioning
confidence: 99%